Determinan Fraudulent Financial Reporting: Perspektif Teori Fraud Pentagon - Rolia Wahasusmiah; Poppy Indriani (Jurnal Ekonomi dan Manajemen, 2020)
Cheating in financial statements is done intentionally presenting and manipulating the value of material can mislead stakeholders in decision making for the company.  The research aims to indicate and analyze the influence of fraudulent financial reporting by testing elements of fraud in the Pentagon fraud theory in manufacturing companies listed on the Indonesia Stock Exchange period 2013-2018. The independent variables used in this study were the the Pentagon fraud with the five elements of the indicator which is pressure, Opportunity (opportunity), rationalization (rationalization), competence (competence), and arrogance The dependent variable used is the fraudulent financial reporting that is proscribed with the F-Score. This form of research is quantitative using the company's annual report data and library studies. The analytical techniques described in this study used multiple linear regression. The results of this study stated that financial stability, financial target and external pressure have a significant influence on fraudulent financial reporting. While Institutional ownership, Ineffective monitoring, quality of external auditors, Change in auditor, change in direction, frequent number of CEO's picture has no effect on fraudulent financial reporting.   Keywords: Fraud pentagon theory, fraudulent financial reporting, institutional ownership,